Pengaruh Content Marketing dan Viral Marketing Terhadap Keputusan Pembelian Produk Serum Hanasui di TikTok (Studi pada Followers Akun TikTok @officialhanasui) - Rosiana Avinda Febrianti; Mohammad Maskan; Rizky Kurniawan Murtiyanto (Teewan Journal Solutions, 2025)
The rapid development of digital technology in Indonesia has influenced consumer behavior. One of the developments is the popularity of TikTok. Amid the intense competition in the skincare industry and the widespread issue of overclaiming, Hanasui has faced challenges in maintaining competitiveness. The study aims to analyze the influence of content marketing and viral marketing on the purchase decision of Hanasui serum products on TikTok. This research was an explanatory quantitative study. The data were collected through questionnaires distributed to 100 respondents who were the followers of @officialhanasui TikTok account. The sampling technique used a non-probability sampling method with purposive sampling. The data analysis in this study employed multiple regression analysis and hypothesis testing. The results of this study showed that content marketing and viral marketing both partially and simultaneously had a positive and significant influenced on purchasing decisions. Based on the findings of this study, it is concluded that Hanasui is advised to continuously optimize effective content marketing and viral marketing strategies to strengthen consumers purchase decisions regarding Hanasui serum products on the TikTok platform.